2016
DOI: 10.1088/1367-2630/18/3/033017
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of lattice thermal conductivity of Td–WTe2

Abstract: The structural and thermal properties of bulk Td-WTe 2 have been studied by using first-principles calculations based on the simple Klemens model and an iterative self-consistent method. Both methods show that lattice thermal conductivity is anisotropic, with the highest value in the (001) plane, and lowest one along the c-axis at 300 K. The calculated average thermal conductivity of WTe 2 is in agreement with the experimental measurement. The size dependent thermal conductivity shows that nanostructuring of W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 61 publications
7
44
0
1
Order By: Relevance
“…Since phase transition has also been used for enhancing thermoelectric figure of merit (ZT) for other calcogenides like SnSe 51 , Cu2Se 52 and so on, such a phase transition of 2H to Td could potentially result in a higher ZT factor due to the decreased thermal conductivity both along the in-plane direction and the cross-plane direction. 43 and Liu et al, 48 and measurement by Jiang et al, 39 Chiritescu et al, 44 Murato et al 45 , Zhou et al, 46 Brixner et al 49 and Jana et al 50 In Figure 4, we show the temperature-dependent and of the 2H WSe1.2Te0.8 (x=0.4) and…”
mentioning
confidence: 76%
“…Since phase transition has also been used for enhancing thermoelectric figure of merit (ZT) for other calcogenides like SnSe 51 , Cu2Se 52 and so on, such a phase transition of 2H to Td could potentially result in a higher ZT factor due to the decreased thermal conductivity both along the in-plane direction and the cross-plane direction. 43 and Liu et al, 48 and measurement by Jiang et al, 39 Chiritescu et al, 44 Murato et al 45 , Zhou et al, 46 Brixner et al 49 and Jana et al 50 In Figure 4, we show the temperature-dependent and of the 2H WSe1.2Te0.8 (x=0.4) and…”
mentioning
confidence: 76%
“…One effective approach to improve the performance of thermoelectric and thermal insulating materials is to lower the thermal conductivity without impacting the electronic properties. [16] In contrast, Ma et al revealed that the calculated anisotropic thermal conductivity of monolayer Td-WTe 2 has its maximum value along the b-axis. [14] Semimetal Td-WTe 2 is theoretically predicted to have a low thermal conductivity because of its heavy atomic mass and low Debye temperature, which makes it a prominent candidate for thermoelectric materials.…”
Section: Doi: 101002/adma201804979mentioning
confidence: 92%
“…Moreover, Kanatzidis and coworkers reported a high ZT of 2.6 ± 0.3 at 923 K along the zigzag direction of bulk SnSe, such enhancement of thermoelectric efficiency is due to the anharmonic and anisotropic bonds and intrinsically ultralow thermal conductivity. Other low‐symmetric 2D materials with low thermal conductivities and highly anisotropic transport properties, including WTe 2 , and TiS 3 also show potential promising thermoelectric application.…”
Section: Applicationsmentioning
confidence: 99%